Right to Education and Personal Well-Being in the Age of Neoliberalism - Spajić-Vrkaš, Vedrana (Array, 2009)
The process of commercialization has penetrated every aspect of life, including education. In the New World Order governed by globalization and neoliberal policies teaching and learning are seen as a huge market of about two trillion dollars ruled by the cost-and-benefit logic and reduced to edutainment with unprecedented consequences for the wellbeing of the individual, societies and the planet. Traditionally, education has been understood as the key instrument of inter-generational transmission of knowledge and skills valued by a particular society. By being in a service of the society education is said to contribute to the well-being of the society’s members and the government is held responsible by its citizens for maintaining and regulating educational provisions to balance these ends. After the recognition of education as a human right by the international human rights law and the establishment of the permanent system of reporting on the implementation of international standards in education, national governments have become internationally responsible for the availability, accessibility, acceptability and adaptability of educational services to progressively ensure that all its citizens learn and are taught equally. The fulfillment of national and international obligations by governments have, nonetheless, become problematic in the context of the international trade law which defines education not as a human rights but as a trading service. The establishment of WTO and the enforcement of GATS policies aiming at eliminating all barriers to the free flow of trade in goods, capital and services, including education, nullify the very international standards in education by, in the one hand, turning education into commodity and, in the other hand, by reducing the authority of the state over educational sector, which threatens to broaden the gap between those who are able to purchase the services and those who are not. These policies have detrimental effects on developing and transitional countries in which the international financial organizations are primarily interested due to their largely unmet and expanding educational needs. The result is that the scope and content of educational restructuring in those countries are imposed on their governments through a fixed system of conditional and time-bounded international political and financial pressures. These pressures are legitimized and justified by the myth of the catch-all globalization, i.e. of the possibility of achieving global competitiveness by strictly following a fixed systems of externally defined conditions that are neither contextualized nor accompanied by for the country adequate strategies and resources. The result is that the burden of promoting complex and extremely expensive educational restructuring is on national and local governments which are being marginalized as international actors and thus left unprepared for achieving a necessary balance between national interests and international obligations. Drawing from critical narratives and the discourses of critical educators the presentation will analyze the impact of neoliberal policies on educational changes in Croatia with special focus on voices and modes of resistance.